Meteotsunamis at the Río de la Plata estuary. (31st October 2022) - Perez, Iael; Dragani, Walter; Oreiro, Fernando; Fiore, Mónica
Abstract: A recent numerical study showed that low-amplitude meteotsunamis could be detected at the Río de la Plata (RDP) estuary. In this work, eight sea level series (one year long, 2018) were analyzed: six measured within the RDP estuary and two at the adjacent continental shelf. All meteotsunami events during 2018 were identified and analyzed at the RDP estuary, and the maximum wave height observed was 0.78 m. The atmospheric conditions during the analyzed events were investigated, showing that the presence of atmospheric cold fronts and atmospheric gravity waves seem to happen simultaneously with meteotsunami events. From sea-level observations gathered at the estuary it was inferred that the meteotsunamis could be driven by atmospheric forcings propagating (i) mainly from SE to NW (the meteotsunami would be driven along the estuary from the outer to the upper RDP, and the Proudman resonance mechanism could explain its amplification), (ii) predominantly from SW to NE (the meteotsunami would be simultaneously generated at different locations of the RDP estuary), or (iii) the meteotsunami could be generated in waters of the continental shelf, to get into the RDP estuary, and then freely propagates from the outer to the upper RDP (in this case the Proudman resonance mechanism would not explain the amplification within the estuary). It is important to mention that the results of the present investigation are biased to the high-period band of meteotsunamis because the sampling interval (20 min, for most locations) is rather large to allow the study of the whole meteotsunami frequency band. Graphical abstract: Image 1 Highlights: Meteotsunamis were detected at the Río de la Plata (RDP) estuary for the first time. The maximum meteotsunami wave height observed at the estuary was 0.78 m. Meteotsunamis at the RDP could be driven by atmospheric gravity waves (AGW). Meteotsunamis detected at the RDP could be originated inside or outside the estuary. The propagation of the meteotsunamis depends on the AGW propagation direction.